2014
DOI: 10.1002/ajp.22325
|View full text |Cite
|
Sign up to set email alerts
|

Pitheciids in fragmented habitats: Land cover change and its implications for conservation

Abstract: Pitheciids (Cacajao, Callicebus, Chiropotes, and Pithecia) have experienced habitat loss and fragmentation across their geographic range in South America. Some populations living in habitat fragments live in smaller groups, travel shorter distances, and consume items that are not regularly found in the diets of populations living in continuous habitat; however, these patterns are not consistent across species. I used the IUCN Red List of Threatened Species to delineate the geographic range and conservation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 124 publications
0
12
0
Order By: Relevance
“…Pitheciid genera consume fruit from a large number of plant genera, which is to be expected given the large geographic ranges of the four genera [Boyle, ], the diversity of habitats found within these ranges [Silva Júnior et al, ], and the morphological adaptations that allow pitheciids to consume ripe and unripe fruit parts [Kinzey, ; Norconk et al, ]. We found that 1) Chiropotes and Pithecia fruit lists were the most similar to each other and Callicebus fruit lists were the least similar to the fruit lists of the other genera; 2) overall, and for Callicebus and Chiropotes , fruit lists from locations in close proximity had greater similarities than lists from study sites that were further apart; and 3) fruit lists from forest fragments and continuous forest did not differ in the number of fruit genera used by the pitheciids.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Pitheciid genera consume fruit from a large number of plant genera, which is to be expected given the large geographic ranges of the four genera [Boyle, ], the diversity of habitats found within these ranges [Silva Júnior et al, ], and the morphological adaptations that allow pitheciids to consume ripe and unripe fruit parts [Kinzey, ; Norconk et al, ]. We found that 1) Chiropotes and Pithecia fruit lists were the most similar to each other and Callicebus fruit lists were the least similar to the fruit lists of the other genera; 2) overall, and for Callicebus and Chiropotes , fruit lists from locations in close proximity had greater similarities than lists from study sites that were further apart; and 3) fruit lists from forest fragments and continuous forest did not differ in the number of fruit genera used by the pitheciids.…”
Section: Discussionmentioning
confidence: 61%
“…The geographic distribution of the pitheciids covers 600 million ha in 10 South American countries [Boyle, ; IUCN, ]. Among pitheciids, Cacajao has the smallest total geographic range and Callicebus the largest, and the range of Callicebus extends beyond that of other pitheciids in approximately 25% of its geographic range (i.e., southern Bolivia, Paraguay, southwestern Brazil, Atlantic Forest of Brazil) [Boyle, ; IUCN, ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The taxonomy of Neotropical primates has changed considerably in the past few years, reflecting current research efforts focusing on the group across the South American continent. Although Paraguayan specimens have been used in regional studies including morphology (Arístide et al 2014), genetics (Matayoshi et al 1986;Mudry et al 1987;Pargament and Slavutsky 1987;Martínez et al 2004;Mudry et al 2007;Casado et al 2010), phylogenetics and phylogeography (Hoyos et al 2016), ecology (Boyle 2014) and zoonosis (Díaz et al 2007), little research has been done on this group within Paraguay; the few works available focus on rare or uncommon species such as Mico melanurus (Stallings and Mittermeier 1983), Aotus azarae , and on the more common Alouatta caraya (Giordano and Ballard 2010). Conservation status of primates in Paraguay was assessed by Stallings (1985) and Rumiz and Stallings (1989) and has not been revised since.…”
Section: Discussionmentioning
confidence: 99%